Who Teaches Writing - Branson, Tyler; Brooks, Ron; Cadman, Dana; Cephus, Heidi; Childers, Sara Beth; Devore, Elizabeth; Sicari, Anna; Hogg, Charlotte; Horton, Ho'omana Nathan (Open textbook library., 2021)
Who Teaches Writing is an open teaching and learning resource being used in English Composition classes at Oklahoma State University. It was authored by contributors from Oklahoma State University and also includes invited chapters from faculty and staff at institutions both inside and outside of Oklahoma. Contributors include faculty from various departments, contingent faculty and staff, and graduate instructors. One purpose of the resource is to provide short, relatively jargon-free chapters geared toward undergraduate students taking First-Year Composition. Support for this project was provided in part by OpenOKState and Oklahoma State University Libraries.